(untitled) (Journal of Social Sciences Review, 2022)
In Pakistani TV talk shows like “Khabardar”, power issues are illuminated, and various hidden ideologies are deconstructed for the achievement of hidden goals; it is the most popular and fascinating way to convey the ideas, perceptions, and effects of the various political statements from the leaders’ perspectives in the current scenario and circumstances. Such types of practices are decorated more with sophisticated vocabulary, witty compliments, and discursive linguistics strategies by character portrayal, particularly as in the characters of “Khabardar,” Critical discourse analysis is a linguistic tool which is helpful to reveal the such type of manipulation as it is displayed in “Khabardar” and CDA also clarifies how and why the characters are being criticized. Actually, the characters in talk shows like “Khabardar” are intentionally revealing their ignorance of linguistic phenomena as well as convey real facts about social and political systems through witty remarks. Through CDA, the current study is centred on political and social scenarios for the illumination of hidden language games. This research is purely qualitative based on Fairclough’s three-dimensional models and critically analyzes “Khabardar,” three episodes for sociopolitical elements and language games with the help of CDA.